2015
DOI: 10.1159/000430171
|View full text |Cite
|
Sign up to set email alerts
|

Valsartan Reduced Atrial Fibrillation Susceptibility by Inhibiting Atrial Parasympathetic Remodeling through MAPKs/Neurturin Pathway

Abstract: Background/Aims: Angiotensin II receptor blockers (ARBs) have been proved to be effective in preventing atrial structural and electrical remodelinq in atrial fibrillation (AF). Previous studies have shown that parasympathetic remodeling plays an important role in AF. However, the effects of ARBs on atrial parasympathetic remodeling in AF and the underlying mechanisms are still unknown. Methods: Canines were divided into sham-operated, pacing and valsartan + pacing groups. Rats and HL-1 cardiomyocytes were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…DAG activates protein kinase C, which in turn activates extracellular-signal-regulated kinases (ERKs). In addition, acting as a potent NADPH oxidase activator, Ang II induces ROS overproduction, which, in-turn, activates multiple downstream second messengers, including MAPK, nuclear factor-κB and cytokines (52,53). Through the activation of the MAPK signalling pathway, Ang II promotes the secretion of TGF-β 1 .…”
Section: Renin-ang-aldosterone System (Raas)mentioning
confidence: 99%
“…DAG activates protein kinase C, which in turn activates extracellular-signal-regulated kinases (ERKs). In addition, acting as a potent NADPH oxidase activator, Ang II induces ROS overproduction, which, in-turn, activates multiple downstream second messengers, including MAPK, nuclear factor-κB and cytokines (52,53). Through the activation of the MAPK signalling pathway, Ang II promotes the secretion of TGF-β 1 .…”
Section: Renin-ang-aldosterone System (Raas)mentioning
confidence: 99%
“…Ang II induces reactive oxygen species (ROS) generation, which activates multiple intracellular second messenger molecules such as mitogen-activated protein kinases (MAPK), transforming growth factor-β1 (TGF-β1), nuclear factor-κB (NF-κB), and cytokines, including interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor α (TNFα) 11 , 12 . The MAPK pathway, including c-Jun N-terminal kinase (JNK) activation, is associated with various pathological conditions such as cancer, stroke, inflammatory disease, and heart failure 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (43) revealed that the MAPKs/TGF-β1/TRAF6 signaling pathways participate in atrial fibrosis in patients with rheumatic heart disease, causing the occurrence of AF following cardiac surgery. Inhibiting the MAPK pathways can prevent atrial parasympathetic remodeling and the occurrence of AF (44). The induction of AF and structural remodeling was associated with MAPK expression and the decrease in collagenase activity (15).…”
Section: Discussionmentioning
confidence: 99%